Targeting Strategies for Enhancing Paclitaxel Specificity in Chemotherapy - Ma, Yuan; Yu, Sifan; Ni, Shuaijian; Zhang, Baoxian; Kung, Angela Chun Fai; Gao, Jin; Lu, Aiping; Zhang, Ge (Frontiers in Cell and Developmental Biology, 2021)
Paclitaxel (PTX) has been used for cancer treatment over decades, becoming one of the most successful chemotherapeutics in clinic and finance. However, serious problems still exist owing to the poor solubility and non-selective toxicity of PTX. In respect of these issues, recent advances have addressed the water solubility and tumor-specificity related to PTX application. There have been plenty of measures raised to remedy the limitations by enhancing tumor recognition via ligand-receptor mediated targeting as well as other associated strategies. In this review, we conducted various kinds of ligands emerged as PTX tumor-targeting tools. Especially, the article highlighted small molecules, proteins and aptamers functionalized conjugates and nanoparticles, providing a promising approach for PTX-based individualized treatment in the prospects.